The IASP classification of chronic pain for ICD-11 - functioning properties of chronic pain - Nugraha, Boya; Gutenbrunner, Christoph; Barke, Antonia; Karst, Matthias; Schiller, Jorg; Schaefer, Peter; Falter, Silke; Korwisi, Beatrice; Rief, Winfried; Treede, Rolf-Detlef (Pain, 2019)
Physical, mental, and social well-being are part of the concept of health according to the World Health Organization, in addition to the absence of disease and infirmity. Therefore, for a full description of a person's health status, the International Classification of Functioning, Disability and Health (ICF) was launched in 2001 to complement the existing International Classification of Diseases (ICD). The 11th version of the ICD (ICD-11) is based on so-called content models, which have 13 main parameters. One of them is functioning properties (FPs) that, according to the WHO, consist of the activities and participation components of the ICE. Recently, chronic pain codes were added to the 11th edition of the ICD, and hence, a specific set of FPs for chronic pain is required as a link to the ICF. In addition, pain is one of the 7 dimensions of the generic set of the ICF, which applies to any person. Thus, assessment and management of pain are also important for the implementation of the ICF in general. This article describes the current consensus proposal by the International Association for the Study of Pain (IASP) and the International Society of Physical and Rehabilitation Medicine (ISPRM) for a specific set of FPs of chronic pain, which will have to be empirically validated in a next step. The combined use of ICD-11 and ICF is expected to improve research reports on chronic pain by a more precise and adequate coding, as well as patient management through better diagnostic classification.